2013
DOI: 10.1002/bmb.20769
|View full text |Cite
|
Sign up to set email alerts
|

An inquiry‐based biochemistry laboratory structure emphasizing competency in the scientific process: A guided approach with an electronic notebook format

Abstract: The laboratory setting is an exciting and gratifying place to teach because you can actively engage the students in the learning process through hands-on activities; it is a dynamic environment amenable to collaborative work, critical thinking, problem-solving and discovery. The guided inquiry-based approach described here guides the students through their laboratory work at a steady pace that encourages them to focus on quality observations, careful data collection and thought processes surrounding the chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Pedagogically, protocol writing is an exercise in translating theoretical concepts to an experimental procedure. The collective revision of protocol by students and instructor lends well to hands-on, inquiry-based learning [ 17 ]. Unlike PLNs, LabArchives allows for multiple revisions and the final version is clear and legible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedagogically, protocol writing is an exercise in translating theoretical concepts to an experimental procedure. The collective revision of protocol by students and instructor lends well to hands-on, inquiry-based learning [ 17 ]. Unlike PLNs, LabArchives allows for multiple revisions and the final version is clear and legible.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include the use of Evernote, Googledocs, Microsoft OneNote, and web blogs as ELNs [ 13 16 ]. In addition, the following studies on inclusion of ELN in teaching laboratories have been reported in the literature: An ELN based on the Sakai software was used in an inquiry-based biochemistry teaching laboratory course [ 17 ], and the Pebblepad ePortfolio system was used as ELN in a biochemistry and molecular biology lab course [ 18 ]. Weibel described the use of Googledocs for a paperless undergraduate physical chemistry teaching laboratory [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, others have noted that transitioning students from “cookbook” style laboratories to inquiry driven ones is not as simple as it first appears. This leap can be facilitated by guided inquiry, a method that is in between using stepwise procedures and open‐inquiry learning .…”
Section: Introductionmentioning
confidence: 99%
“…While using inquiry approaches or CUREs in biochemistry teaching labs can produce learning gains, fundamental training and understanding of lab techniques remains an essential part of lab education. [7][8][9] In the first half of our one-credit, semester-long biochemistry lab course, students complete scripted experiments involving enzyme expression, purification, and basic characterization. The second half consists of guided or open inquiry projects.…”
Section: Introductionmentioning
confidence: 99%